Accounting Information System Effectiveness: Improvement Of Education And Training Services At Olx Autos Bandung - Asep Effendi (Jurnal Mantik, 2020)
Rapid development of technology and information, everything becomes more effective and efficient. In addition, the current communication process can also be done easily even without the limitations of a country, it can be useful for business activities because it can facilitate the acquisition of information, One type of information system that is most widely used by humans in this era is the Accounting Information System (DRAIN). AIS is a system that collects, records, records, stores, and processes data to produce accounting information for decision makers, Accounting Information System (AIS) is a collection of human resources (HR) and capital that has the task of preparing financial information and information. This study aims to determine how much influence user participation, education and training have on the effectiveness of the Accounting Information System conducted at the OLX Autos Bandungcompany. The research method used is descriptive and verification methods with a quantitative approach. The population in this study were 30 respondents at OLX Autos Bandungwho used the Accounting Information System. The sampling technique used is a non-probability sampling technique with a saturated sampling method. The method of data analysis in this study uses multiple linear regression analysis which is tested using SPSS 24.0 software for windows. The results of hypothesis testing in this study indicate that (1) User Participation has a positive and significant effect on the effectiveness of the Accounting Information System, and (2) Education and Training has a positive and significant influence on the Effectiveness of the Accounting Information System at OLX Autos Bandung